Epistemic Pluralism: The Missing Link and the Ambitions of Epistemology. (21st July 2020) - Zangwill, Nick
Abstract: In this paper epistemic pluralism concerning knowledge is taken to be the claim that very different facts may constitute knowledge. The paper argues for pluralism by arguing that very different facts can constitute the knowledge‐making links between beliefs and facts. If pluralism is right, we need not anxiously seek a unified account of the links between beliefs and facts that partly constitute knowledge in different cases of knowledge. The paper argues that no good reasons have been put forward in favour of believing in a unified maker of knowledge. It then appeals to the role of knowledge in order to argue that we have positive reason to embrace pluralism.